Peran PT Sirtu Karya Utama Dalam Meningkatkan Kesejahteraan Masyarakat Di Kelurahan Buluri - Nurfitriani, Nurfitriani (Scimadly Publishing, 2022)
With the mining company C PT. Sirtukarya Utama has an impact on the welfare of the people of Buluri Village. Based on this, the researcher is interested in raising this issue in the form of a thesis with the title